An exploratory analysis of losing possession in professional soccer - Shafizadeh, M.; Gray, S.; Sproule, J.; McMorris, T. (Journal of Quantitative Analysis in Sports, 2012)
The aim of the present study was to develop a measure that determines the reasons for losing possession in professional soccer. Fifty five national soccer teams that took part in 2006 and 2010 World Cup games were selected for this study. The Losing Possession Observational Checklist for Soccer was developed and applied to games in these tournaments. The results of interrater and intra-rater reliabilities showed that the new checklist had good stability (K= .75) and objectivity (K= .75). In addition, the results of exploratory factor analyses showed that losing possession in soccer included skill execution and parameterization, skill under stress, and speed and timing problems that accounted for 77% of common variance. In conclusion, current findings demonstrated that losing possession in soccer is multidimensional in nature and consists of motor and cognitive factors on the basis of specialist and statistical confirmation.